Is there really only “regression”?——Rethinking Adorno 's Multidimensional Critique of Stravinsky (Journal of Global Arts Studies, 2024)
Background: Since the twentieth century, Chinese musicologists have increasingly emphasized the relationship between music and society, and between music and philosophy, with Adorno being a key figure in scholars' discussions. Purpose: The purpose of this paper is to elaborate Adorno’s dialectical evaluation and multidimensional perspective on Stravinsky. Methods: Based on the research of domestic scholars on Adorno’s “retrogressive” evaluation of Stravinsky, this paper finds that scholars mainly elaborate Adorno’s critical evaluation of Stravinsky, ignoring the correlation between Adorno’s affirmative premise that Stravinsky is a representative of new music and his multidimensional critique of musicianship, sociability, and philosophicality, as well as the dimensions of the critique. Results: The study reveals Adorno’s path of social critique through musical form as a critique of social mediation. Conclusion: In the process of evaluating Stravinsky, Adorno, based on the analysis of musical works and combined with sociology and philosophy, emphasizes the cognitive function of musical works, providing a highly composite and dialectical perspective for the study of musicology.
Keywords: Theodor Adorno; Stravinsky; regression; dialecticality